Evaluating the Efficiency of Sustainable Suppliers Based on Human and Environmental Indicators Using Data Envelopment Analysis and Gap Analysis (Case Study: Petrochemical Companies) - Karamad, Somayeh; Dehghan Dehnavi, Hassan; Babaei Meybodi, Hamid; Rabbani, Mojdeh (Management Strategies and Engineering Sciences, 2024)
Evaluating the efficiency of sustainable suppliers not only raises awareness among stakeholders but also enhances competition, promotes industry dynamism, and fosters the sustainable and balanced development of society. In the present study, human and environmental indicators were utilized, and optimal input and output criteria were selected based on expert opinions. Therefore, the selection of variables (inputs and outputs) in this research was assessed through a review of similar studies, interviews, and surveys with experts and specialists. All calculations were performed using DEA Solver software. The results revealed that out of 13 companies, 12 were efficient (efficiency score equal to one), and only one company was inefficient. Furthermore, "Movaledan Chemical Company," with an efficiency score of 1.66, was found to be more efficient compared to other companies, almost twice as efficient as "Pars Pak Kimia Company," which had the lowest efficiency score of 0.858. Pars Pak Kimia Company, with the lowest efficiency score (0.858), ranked last. In Data Envelopment Analysis (DEA), when calculating the efficiency of companies, several efficient units were used as benchmarks (or references) for each inefficient company. The benchmarks for Pars Pak Kimia Company were "Iran Petrochemical Trading Company" with a lambda coefficient of 0.262, "Chelik Alborz Company" with a lambda coefficient of 0.55, "Movaledan Chemical Company" with a lambda coefficient of 0.052, and "Farzam Chemical Group" with a lambda coefficient of 0.135. The results of the paired T-test indicate a significant difference at the 95% confidence level between the scores of this variable in the current and target states.